Neuro – Linguistic Programming dan Research Metodology sebagai Penggalian Informasi Warga Binaan Pemasyarakatan - Rama Fatahillah Yulianto (Program Studi Hukum Universitas Pamulang, 2020)
Inmates residents have the right to get teaching and education, while correctional officers have the obligation to provide guidance to WBP. A good coaching pattern needs an assessment so that a subjective pattern of guidance can be formulated, because the criminal background of each prisoner is different, plus the psychological condition of each individual is different. Research Methodology and Neuro - Linguistic Programming needs to be known and mastered by the task force, especially the assessor. Lawbreakers are not always cooperative, besides the condition of the perpetrators who tend to close themselves off from the environment. So that it will be difficult assessor for theto dig up information from himself concerned. This study uses a literature review aimed at identifying treatment models that are appropriate for the development programs at each prison, detention center, and LPKA. So it is hoped that before the WBP is placed in the mass of each correctional unit concerned, ancan be carried out assessment so that the coaching method can be targeted at the right person. In addition, it is hoped that after being free they can integrate with the community and have the same abilities as children outside the institution, as well as improve the self-concept possessed by WBP. The benefits of this study can provide input in the formulation of policies regarding effective methods of extracting information to be applied in Indonesian Correctional Unit.